Physiology and pathophysiology of microglia - Hanisch, Uwe-Karsten (Henry Stewart Talks, 2012)
Physiology and pathophysiology of microglia, Microglia, resident innate immune cells of the CNS, Approaches to the study of microglia, Developmental origin and functions, Developmental contributions and consequences of malfunction, The concept of 'resting' microglia, functions in the healthy adult CNS, Tissue surveillance and synaptic nursing as house-keeping duties, The concept of microglial 'activation', transformation to distinct activity states, The concept of detrimental microglia, Activation signals and response diversity, Macrophages and microglia: diversity in response behaviour, Elements of the microglial response repertoire, Response dynamics, Microglial phenotypes associated with phagocytosis, Contributions of microglia in neurodegenerative diseases